Study of Some Markers of Oxidative Stress Statues in Cardiovascular Disease Patients - H, Yasmeen Muhialdeen; Jawad, Alaa H; Al-Hashemi, Wisam Kadhum H (Al-Nahrain Journal of Science, 2018)
The oxidative stress is one of the main cause for cardiovascular diseases and also one of the results of these diseases, its development. The aim of this study was to investigate the relationship between of some oxidative stress markers and cardiovascular diseases. This study involved 84 samples matched ages and sex divided into groups; 28 samples cardiovascular and 28 hypertensive in addition to 28 healthy control group. The following analysis were done: lipid profile, malondialdehyde (MDA), and albumin. The results show there is a significant increase in lipid profile between each group and control group. MDA was significantly higher in patients compared to controls whereas no significant difference was found in albumin between patient and control groups. The increase in MDA which is a product of lipid peroxidation is attributed to destruction in body cell caused by free radicals and resulting oxidative stress. It has been concluded that the assessing the lipid ratios is important even in a normal individual as it is one of the factors for development of cardiovascular diseases and their complications. There is a positive relation between oxidation results from these diseases and their developments.